SMART DIE CASTING FOUNDRY ACCORDING TO INDUSTRIAL REVOLUTION 4 - Vanli, Ali Serdar; Akdogan, Anil; Kerber, Kai; Ozbek, Sahin; Durakbasa, M. Numan (TECHNICAL UNIV CLUJ-NAPOCA, FAC MACHINE BUILDING DEPT SYSTEMS ENG, 2018)
Nowadays, there are reports in the specialist media of so-called Industrial Revolution 4.0. According to this industrial revolution, the production is increasingly digitized and even component-driven production is mentioned. Additionally, production machines exchange extensive process data with one another and enormous amounts of data are analyzed for production optimization. These challenges will also be faced by the die casting industry. A smart die casting foundry, according to the definition of Industry 4.0, is a highly flexible production system that is able to produce small lot sizes and even single parts. To realize this foundry, various tools and concepts need to be adapted. The use of modern information technology and the flexibilization of machines and processes are necessary to achieve this goal. If machine and process data are accessible without barriers, there are lots of possibilities to link these and to carry out comprehensive optimization along the process chain of die casting. The logistics and processes of the foundry should be transparent and can be tracked at any time. The point of consumption of energy and resources are need to be visible, the material flows can be analyzed and optimized in detail. Complex interactions can also be deciphered and the entire system can be adjusted to an optimum operating point. To realize this vision there is still some challenges. Within the scope of this paper, practical potentials of different technologies and tools are presented with the adaption of Industry 4.0 to the die casting technology and production.
Keywords: Industrial Revolution 4.0; Die Casting; Smart Foundry; Mechanics